Technology and banking operations: Perspectives of international students in a Ghanaian University - Hanatou Laya Moussa; Anita Bans-Akutey (goodwood publishing, 2022)
Purpose: The study analysed perceptions of international students in a Ghanaian private university college on the effect of information technology on banking operations as they have experienced it in Ghana. Research methodology: A mixed methods research approach was used for this study. Data were collected from 60 international students who were sampled randomly from the population of international students in the college. Descriptive statistics from IBM SPSS Statistics 24 was used to analyse quantitative data, while thematic analysis was used to analyse qualitative data. Results: Findings showed that even though information technology affects banking operations positively by making operations efficient, easier and faster for both employees and customers; it has increased the rate of fraudulent banking activities. This has exposed clients and employees alike, to a higher risk of fraud and other fraud-related activities. Limitations: This study was limited to international students of a private university college in Ghana. Data were collected from an online survey; hence a limitation to the number of international students who participated in the study. Contribution: Despite the fact that information technology influences banking operations in Ghana positively, it has resulted in increased fraudulent activities related to banking operations. This requires that policymakers improve online security in the banking space. Novelty: There is an emphasis that though technology’s use in banking operations has a positive effect, it also presents banking institutions with an increased risk of fraud as perceived by international students schooling in a private tertiary institution in Ghana.